2015
DOI: 10.3329/bjms.v14i4.25766
|View full text |Cite
|
Sign up to set email alerts
|

Injuries among Drivers in RTA

Abstract: Abstracts:Background: Road Traffic Accidents (RTA) are responsible for the greatest number of injuries and fatalities worldwide by killing around 1.2 million people each year and injuring another 50 million. Objective: To evaluate the present situation of Road Traffic Accidents (RTA) in Dhaka and to find out the pattern of injuries present in the bodies of drivers who were victims of fatal RTA. Materials & Method: This cross sectional descriptive study was conducted at the Dhaka Medical College (DMC) Morgue du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Pedestrians of different age groups were found to be most vulnerable to RTCs. [15][16][17] It was a leading cause of unintentional injuries in children 18,19 and a leading cause of fatal injury among adults aged 25-64 years for both males and females. 20 Males were found more vulnerable than females.…”
Section: Characteristics Of Rtcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedestrians of different age groups were found to be most vulnerable to RTCs. [15][16][17] It was a leading cause of unintentional injuries in children 18,19 and a leading cause of fatal injury among adults aged 25-64 years for both males and females. 20 Males were found more vulnerable than females.…”
Section: Characteristics Of Rtcsmentioning
confidence: 99%
“…18,[20][21][22] Buses were found to cause the most crashes, while rickshaws were in frequent accidents on urban roads. 17,23,24 Of RTC victims, 31% stated that crashes were happening even when the vehicles were driving at an average speed because most drivers (55%) drove on the wrong side of the road. 25 At the district level, a peripheral tertiary hospital observed that 12% of the RTC victims suffered injuries from makeshift 3-wheelers, locally known as nasimon and karimon, which have been illegally riding on district highways.…”
Section: Characteristics Of Rtcsmentioning
confidence: 99%